On Men and Forests - Machado, Luciana de Oliveira Rosa (Sustainability in Debate, 2014)
Emílio Moran; Elinor Ostrom. Ecossistemas Florestais: interação homem-ambiente. São Paulo: Editora Senac São Paulo; Edusp, 2009. 544p. Tradução de Diógenes S. Alves. ISBN 9788573597905 (Editora Senac São Paulo) 9788531411342 (Edusp). Título original: Seeing the Forest and the Trees: Human-Environment Interactions in Forest Ecosystems.